You are on page 1of 118

VECTOR FUNCTIONS

VECTOR FUNCTIONS

12.4
Motion in Space:
Velocity and Acceleration
In this section, we will learn about:
The motion of an object
using tangent and normal vectors.

Here, we show how the ideas of tangent

and normal vectors and curvature can be
used in physics to study:
The motion of an object, including its velocity
and acceleration, along a space curve.

In particular, we follow in the footsteps of

Newton by using these methods to derive
Keplers First Law of planetary motion.

VELOCITY

Suppose a particle moves through

space so that its position vector at
time t is r(t).

VELOCITY

Vector 1

Notice from the figure that, for small values

of h, the vector

r (t + h) r (t )
h
approximates
the direction of the
particle moving along
the curve r(t).

VELOCITY

Its magnitude measures the size

of the displacement vector per unit
time.

VELOCITY

The vector 1 gives the average

velocity over a time interval of
length h.

VELOCITY VECTOR

Equation 2

at time t :

r (t + h) r (t )
v (t ) = lim
h 0
h
= r '(t )

VELOCITY VECTOR

Thus, the velocity vector is also

the tangent vector and points in
the direction of the tangent line.

SPEED

The speed of the particle at time t

is the magnitude of the velocity vector,
that is, |v(t)|.

SPEED

This is appropriate because, from Equation 2

and from Equation 7 in Section 12.3,
we have:

ds
| v(t ) |=| r '(t ) |=
dt
= rate of change
of distance with
respect to time

ACCELERATION

As in the case of one-dimensional motion,

the acceleration of the particle is defined as
the derivative of the velocity:
a(t) = v(t) = r(t)

Example 1

The position vector of an object moving

in a plane is given by:
r(t) = t3 i + t2 j
Find its velocity, speed, and acceleration
when t = 1 and illustrate geometrically.

Example 1

The velocity and acceleration at time t

are:
v(t) = r(t) = 3t2 i + 2t j
a(t) = r(t) = 6t I + 2 j

Example 1

The speed at t is:

| v (t ) |= (3t ) + (2t )
2 2

= 9t + 4t
4

VELOCITY & ACCELERATION

Example 1

When t = 1, we have:
v(1) = 3 i + 2 j
a(1) = 6 i + 2 j
|v(1)| = 13

Example 1

are shown here.

Example 2

Find the velocity, acceleration, and

speed of a particle with position vector
r(t) = t2, et, tet

Example 2

VELOCITY & ACCELERATION

v (t ) = r '(t ) = 2t , e , (1 + t )e
t

a(t ) = v '(t ) = 2, e , (2 + t )e
t

| v (t ) |= 4t + e + (1 + t ) e
2

2t

2t

The figure shows the path of the particle in

Example 2 with the velocity and acceleration
vectors when t = 1.

The vector integrals that were introduced in

Section 12.2 can be used to find position
vectors when velocity or acceleration vectors
are known, as in the next example.

Example 3

A moving particle starts at an initial position

r(0) = 1, 0, 0
with initial velocity
v(0) = i j + k
Its acceleration is
a(t) = 4t i + 6t j + k
Find its velocity and position at time t.

Example 3

Since a(t) = v(t), we have:

v(t) = a(t) dt
= (4t i + 6t j + k) dt
=2t2 i + 3t2 j + t k + C

Example 3

To determine the value of the constant

vector C, we use the fact that
v(0) = i j + k

So,
C=ij+ k

VELOCITY & ACCELERATION

Example 3

It follows:
v(t) = 2t2 i + 3t2 j + t k + i j + k
= (2t2 + 1) i + (3t2 1) j + (t + 1) k

Example 3

Since v(t) = r(t), we have:

r(t) = v(t) dt
= [(2t2 + 1) i + (3t2 1) j + (t + 1) k] dt
= (t3 + t) i + (t3 t) j + (t2 + t) k + D

Example 3

Putting t = 0, we find that D = r(0) = i.

So, the position at time t is given by:
r(t) = (t3 + t + 1) i + (t3 t) j + (t2 + t) k

The expression for r(t) that we obtained

in Example 3 was used to plot the path
of the particle here for 0 t 3.

In general, vector integrals allow us

to recover:
Velocity, when acceleration is known
t

v (t ) = v (t0 ) + a(u ) du
t0

Position, when velocity is known

t

r (t ) = r (t0 ) + v (u ) du
t0

If the force that acts on a particle is known,

then the acceleration can be found from
Newtons Second Law of Motion.

The vector version of this law states that if,

at any time t, a force F(t) acts on an object
of mass m producing an acceleration a(t),
then
F(t) = ma(t)

Example 4

An object with mass m that moves in

a circular path with constant angular speed
has position vector
r(t) = a cos t i + a sin t j

Find the force acting on the object and

show that it is directed toward the origin.

Example 4

To find the force, we first need to know

the acceleration:

v(t) = r(t) = a sin t i + a cos t j

a(t) = v(t) = a2 cos t i a2 sin t j

Example 4

Therefore, Newtons Second Law gives

the force as:
F(t) = ma(t)
= m2 (a cos t i + a sin t j)

VELOCITY & ACCELERATION

Example 4

Notice that:
F(t) = m2r(t)
This shows that the force acts in the direction
opposite to the radius vector r(t).

Example 4

Therefore, it points toward

the origin.

CENTRIPETAL FORCE

Example 4

Such a force is called a centripetal

(center-seeking) force.

Example 5

A projectile is fired with:

Angle of elevation
Initial velocity v0

Example 5

Assuming that air resistance is negligible

and the only external force is due to gravity,
find the position function r(t) of the projectile.

Example 5

What value of maximizes the range

(the horizontal distance traveled)?

Example 5

We set up the axes so that the projectile

starts at the origin.

Example 5

As the force due to gravity acts downward,

we have:
F = ma = mg j
where g = |a| 9.8 m/s2.
Therefore, a = g j

Example 5

Since v(t) = a, we have:

v(t) = gt j + C
where C = v(0) = v0.
Therefore,
r(t) = v(t) = gt j + v0

Example 5

Integrating again, we obtain:

r(t) = gt2 j + t v0 + D
However,
D = r(0) = 0

VELOCITY & ACCELERATION

E. g. 5Equation 3

So, the position vector of the projectile

is given by:
r(t) = gt2 j + t v0

Example 5

If we write |v0| = v0 (the initial speed

of the projectile), then
v0 = v0 cos i + v0 sin j
Equation 3 becomes:
r(t) = (v0 cos )t i + [(v0 sin )t gt2] j

VELOCITY & ACCELERATION

E. g. 5Equations 4

Therefore, the parametric equations

of the trajectory are:
x = (v0 cos )t
y = (v0 sin )t gt2

Example 5

If you eliminate t from Equations 4,

you will see that y is a quadratic function
of x.

Example 5

of a parabola.

Example 5

The horizontal distance d is the value

of x when y = 0.

Setting y = 0, we obtain:
t = 0 or t = (2v0 sin )/g

Example 5

That second value of t then gives:

2v0 sin
d = x = (v0 cos )
g
v (2sin cos ) v sin 2
=
=
g
g
2
0

2
0

Clearly, d has its maximum value when

sin 2 = 1, that is, = /4.

Example 6

A projectile is fired with muzzle speed 150 m/s

and angle of elevation 45 from a position
10 m above ground level.
Where does the projectile hit the ground?
With what speed does it do so?

Example 6

If we place the origin at ground level,

the initial position of the projectile is (0, 10).

So, we need to adjust Equations 4

by adding 10 to the expression for y.

Example 6

we have:

x = 150 cos( / 4)t = 75 2 t

y = 10 + 150sin( / 4)t (9.8)t
1
2

= 10 + 75 2 t 4.9t

Example 6

Impact occurs when y = 0, that is,

4.9t2 75 2 t 10 = 0

Solving this quadratic equation (and using

only the positive value of t), we get:

t=
21.74
9.8

Example 6

Then,
x 75 2 (21.74)
2306

So, the projectile hits the ground

about 2,306 m away.

Example 6

The velocity of the projectile is:

v(t ) = r '(t )
= 75 2 i + (75 2 9.8t ) j

Example 6

| v (21.74) |= (75 2) + (75 2 9.8 21.74)

2

151m/s

ACCELERATIONCOMPONENTS

When we study the motion of a particle,

it is often useful to resolve the acceleration
into two components:
Tangential (in the direction of the tangent)
Normal (in the direction of the normal)

ACCELERATIONCOMPONENTS

If we write v = |v| for the speed of the particle,

then

r '(t )
v (t )
v
T(t ) =
=
=
| r '(t ) | | v (t ) | v
Thus,
v = vT

ACCELERATIONCOMPONENTS

Equation 5

If we differentiate both sides of that

equation with respect to t, we get:

a = v ' = v ' T + vT '

ACCELERATIONCOMPONENTS

Equation 6

If we use the expression for the curvature

given by Equation 9 in Section 12.3,
we have:

| T'| | T'|
so | T ' |= v
=
=
|r'|
v

ACCELERATIONCOMPONENTS

The unit normal vector was defined

in Section 12.4 as N = T/ |T|
So, Equation 6 gives:

T ' =| T ' | N = vN

ACCELERATIONCOMPONENTS

Formula/Equation 7

Then, Equation 5 becomes:

a = v 'T + v N
2

ACCELERATIONCOMPONENTS

Equations 8

Writing aT and aN for the tangential and

normal components of acceleration,
we have
a = aTT + aNN
where
aT = v

and

aN = Kv2

ACCELERATIONCOMPONENTS

This resolution is illustrated

here.

ACCELERATIONCOMPONENTS

Lets look at what Formula 7

says.

a = v 'T + v N
2

ACCELERATIONCOMPONENTS

The first thing to notice is that

the binormal vector B is absent.
No matter how an object moves through space,
its acceleration always lies in the plane of T and N
(the osculating plane).
Recall that T gives the direction of motion and
N points in the direction the curve is turning.

ACCELERATIONCOMPONENTS

Next, we notice that:

The tangential component of acceleration is v,
the rate of change of speed.
The normal component of acceleration is v2,
the curvature times the square of the speed.

ACCELERATIONCOMPONENTS

This makes sense if we think of

a passenger in a car.
A sharp turn in a road means a large value
of the curvature .
So, the component of the acceleration perpendicular
to the motion is large and the passenger is thrown
against a car door.

ACCELERATIONCOMPONENTS

High speed around the turn has

the same effect.
In fact, if you double your speed,
aN is increased by a factor of 4.

ACCELERATIONCOMPONENTS

We have expressions for the tangential

and normal components of acceleration in
Equations 8.
However, its desirable to have expressions
that depend only on r, r, and r.

ACCELERATIONCOMPONENTS

Thus, we take the dot product of v = vT

with a as given by Equation 7:
v a = vT (v T + v2N)
= vv T T + v3T N
= vv

(Since T T = 1 and T N = 0)

ACCELERATIONCOMPONENTS

Equation 9

Therefore,

v a
aT = v ' =
v
r '(t ) r "(t )
=
| r '(t ) |

ACCELERATIONCOMPONENTS

Equation 10

Using the formula for curvature given by

Theorem 10 in Section 12.3, we have:

| r '(t ) r "(t ) |
2
aN = v =
| r '(t ) |
3
| r '(t ) |
| r '(t ) r "(t ) |
=
| r '(t ) |
2

ACCELERATIONCOMPONENTS

Example 7

A particle moves with position function

r(t) = t2, t2, t3

Find the tangential and normal

components of acceleration.

ACCELERATIONCOMPONENTS
2

r (t ) = t i + t j + t k
2

r '( t ) = 2 t i + 2 t j + 3 t k
r "( t ) = 2 i + 2 j + 6 t k
| r'( t ) | =

8t + 9t
2

Example 7

Example 7

ACCELERATIONCOMPONENTS

Therefore, Equation 9 gives the tangential

component as:

r '(t ) r "(t )
aT =
| r '(t ) |
=

8t + 18t

8t + 9t
2

ACCELERATIONCOMPONENTS

i
r '(t ) r "(t ) = 2t
2

2t 3t
2

6t

= 6t i 6t j
2

Example 7

Example 7

ACCELERATIONCOMPONENTS

component as:

r '(t ) r "(t )
aN =
| r '(t ) |
=

6 2t

8t + 9t
2

We now describe one of the great

accomplishments of calculus by showing how
the material of this chapter can be used to
prove Keplers laws of planetary motion.

After 20 years of studying the astronomical

observations of the Danish astronomer
Tycho Brahe, the German mathematician and
astronomer Johannes Kepler (15711630)
formulated the following three laws.

A planet revolves around the sun

in an elliptical orbit with the sun at
one focus.

The line joining the sun to

a planet sweeps out equal areas
in equal times.

The square of the period of revolution

of a planet is proportional to the cube
of the length of the major axis of its orbit.

KEPLERS LAWS

In his book Principia Mathematica of 1687,

Sir Isaac Newton was able to show that
these three laws are consequences of
two of his own laws:
Second Law of Motion
Law of Universal Gravitation

In what follows, we prove Keplers

First Law.
The remaining laws are proved
as exercises (with hints).

The gravitational force of the sun on a planet

is so much larger than the forces exerted by
other celestial bodies.

Thus, we can safely ignore all bodies in

the universe except the sun and one planet

We use a coordinate system with the sun

at the origin.
We let r = r(t) be the position vector
of the planet.

Equally well, r could be the position

vector of any of:
The moon
A satellite moving around the earth
A comet moving around a star

The velocity vector is:

v = r
The acceleration vector is:
a = r

We use the following laws of Newton.

Second Law of Motion:

F = ma

Law of Gravitation:

GMm
F= 3 r
r
GMm
= 2 u
r

In the two laws,

F is the gravitational force on the planet
m and M are the masses of the planet and the sun
G is the gravitational constant
r = |r|
u = (1/r)r is the unit vector in the direction of r

First, we show that

the planet moves in
one plane.

By equating the expressions for F in

Newtons two laws, we find that:

GM
a= 3 r
r
So, a is parallel to r.
It follows that r x a = 0.

We use Formula 5 in Theorem 3 in

Section 12.2 to write:

d
(r v ) = r ' v + r v '
dt
= v v + ra
= 0+0
=0

KEPLERS FIRST LAWPROOF

Therefore,
rxv=h
where h is a constant vector.
We may assume that h 0;
that is, r and v are not parallel.

This means that the vector r = r(t) is

perpendicular to h for all values of t.

So, the planet always lies in the plane through

the origin perpendicular to h.

a plane curve.

To prove Keplers First Law, we rewrite

the vector h as follows:

h = r v = rr '
= r u (r u) '
= r u (ru '+ r ' u)
= r (u u ') + rr '(u u)
2

= r (u u ')
2

KEPLERS FIRST LAWPROOF

Then,
GM
2
a h = 2 u (r u u ')
r
= GM u (u u ')
= GM [ (u u ')u (u u)u ']

(Property 6,
Th. 8, Sec. 11.4)

KEPLERS FIRST LAWPROOF

However, u u = |u|2 = 1
Also, |u(t)| = 1

that:
u u = 0

Therefore,

a h = GM u '
Thus,

Equation 11

Integrating both sides of that equation,

we get:

v h = GM u + c
where c is a constant vector.

At this point, it is convenient to choose the

coordinate axes so that the standard basis
vector k points in the direction of the vector h.

As both v x h and u are perpendicular

to h, Equation 11 shows that c lies in
the xy-plane.

This means that we can choose

the x- and y-axes so that the vector i
lies in the direction of c.

If is the angle between c and r,

then (r, ) are polar coordinates of
the planet.

From Equation 11 we have:

r ( v h) = r (GM u + c)
= GM r u + r c
= GMr u u + | r || c | cos
= GMr + rc cos
where c = |c|.

KEPLERS FIRST LAWPROOF

Then,

r ( v h)
r=
GM + c cos
1 r ( v h)
=
GM 1 + e cos
where e = c/(GM).

KEPLERS FIRST LAWPROOF

However,

r ( v h) = (r v ) h
= h h
=| h |

=h
where h = |h|.

Thus,
2

h /(GM )
r=
1 + e cos
2
eh / c
=
1 + e cos

Equation 12

ed
r=
1 + e cos

Comparing with Theorem 6 in Section 10.6,

we see that Equation 12 is the polar equation
of a conic section with:
Focus at the origin
Eccentricity e

a closed curve.

This completes the derivation

of Keplers First Law.

KEPLERS LAWS

The proofs of the three laws show that

the methods of this chapter provide
a powerful tool for describing some
of the laws of nature.